Pengaruh Risiko Kredit dan Risiko Likuiditas terhadap Kinerja Keuangan pada Bank BUMN Periode 2015-2020 - Ragil Noviantika Silitonga; Gusganda Suria Manda (Jurnal Maksipreneur, 2022)
This review intends to look at and investigate credit hazard (NPL) and liquidity hazard (LDR) on monetary execution (ROA) at state-claimed banks for the 2015-2020 period. The sample in this research was four state-owned corporations, namely Bank BRI, Bank BNI, Bank BTN, and Bank Mandiri. This exploration utilizes numerous direct relapse investigation strategies utilizing SPSS 20 program. The free factors in this review are credit hazard which is proxied by Non-Performing Advances (NPL) and liquidity hazard which is proxied by Advance to Stores Proportion (LDR), and the reliant variable in this review is the bank's monetary execution as estimated by Return on Resources (ROA). The results showed that the partial effect credit hazard factors (NPL) have a negative and huge impact on monetary execution (ROA) at state-possessed banks for the 2015-2020 period, and somewhat the liquidity hazard variable (LDR) has a positive and unimportant impact on monetary execution (ROA) at banks. BUMN for the 2015-2020 period. At the same time, the credit hazard (NPL) and liquidity hazard (LDR) factors significantly affect the monetary exhibition (ROA) of state-claimed banks for the 2015-2020 period.